2023
DOI: 10.3389/fpubh.2023.1182127
|View full text |Cite
|
Sign up to set email alerts
|

Associations between blood essential metal mixture and serum uric acid: a cross-sectional study

Dongmei Wang,
Yue Li,
Hualin Duan
et al.

Abstract: IntroductionAlthough several studies have explored the associations between single essential metals and serum uric acid (SUA), the study about the essential metal mixture and the interactions of metals for hyperuricemia remains unclear.MethodsWe performed a cross-sectional study to explore the association of the SUA levels with the blood essential metal mixture, including magnesium (Mg), calcium (Ca), iron (Fe), copper (Cu), zinc (Zn), manganese (Mn) in Chinese community-dwelling adults (n=1039). The multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…The balance of essential elements was crucial to endocrine function [ 6 ]. Our previous studies found that blood magnesium (Mg) was positively associated with serum uric acid, dyslipidemia, and thyroid nodules [ 7 9 ]. What’s more, growing evidence has suggested that the imbalance of essential elements seems to be related to the onset and progression of diabetes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The balance of essential elements was crucial to endocrine function [ 6 ]. Our previous studies found that blood magnesium (Mg) was positively associated with serum uric acid, dyslipidemia, and thyroid nodules [ 7 9 ]. What’s more, growing evidence has suggested that the imbalance of essential elements seems to be related to the onset and progression of diabetes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%